2018
DOI: 10.4314/ijs.v20i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on soil nutrient status, nutrient uptake, protein content and yield of chickpea (<i>Cicer arietinum</i> L.) in north western Ethiopia

Abstract: Field experiment was conducted for two consecutive years (2015 and 2016) in north western Ethiopia to test the effect of Integrated Nutrient Management (INM) on soil nutrient status, nutrient uptake, protein content and yield of chickpea. The experiment comprised of 6 levels of INM treatments (unfertilized, 100% recommended-1 dose of chemical fertilizer (RDF), 6 t compost ha alone or combined with: 75, 50 and 25% RDF). The treatments were arranged in randomized complete block design with three replications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…However, effect of integrated nutrient management in chickpea on the harvest index and seed index was found numerically higher under application of 50% RDF + 2 t VC ha -1 + Bio NP (T 6 ). Similar finding were also recorded by Elamin and Madhavi (2015), Sindhi et al (2016), Shivran et al (2017) and Kemal et al (2018).…”
Section: Yield and Yield Attributessupporting
confidence: 88%
See 1 more Smart Citation
“…However, effect of integrated nutrient management in chickpea on the harvest index and seed index was found numerically higher under application of 50% RDF + 2 t VC ha -1 + Bio NP (T 6 ). Similar finding were also recorded by Elamin and Madhavi (2015), Sindhi et al (2016), Shivran et al (2017) and Kemal et al (2018).…”
Section: Yield and Yield Attributessupporting
confidence: 88%
“…Results further indicated that application of 50% RDF + Bio NP (T 2 ) and 50% RDF + 5 t FYM ha -1 (T 3 ) recorded lower seed yield might be due to reduction of 50% recommended dose of fertilizer in both the treatments and this deduction of 50% RDF was not fulfilled by either Bio NP (Rhizobium + PSB) or 5 t FYM ha -1 in respective treatment. The favourable effect of integration of organic manures, inorganic fertilizers and bio fertilizer on yield of chickpea was also recorded by Tolanur and Badanur (2003), Sindhi et al (2016), Shivran et al (2017), Singh et al (2017 and Kemal et al (2018). Stover yield (kg ha -1 ) was also recorded significantly the highest under application of 50% RDF + 2 t VC ha -1 + Bio NP (T 6 ).…”
Section: Yield and Yield Attributesmentioning
confidence: 59%
“…As for the soil pH, all the treatments were in the range of 4.03-4.23 and there was no significant difference. These findings are in line with the report of Kemal et al (2018).…”
Section: Nutrient Status Of Soilsupporting
confidence: 93%